Pengaruh Pemasaran Online Terhadap Minat Beli Konsumen Pada Toko Jingga - Nini, Nini (Jurnal Pustaka Manajemen (Pusat Akses Kajian Manajemen), 2023)
This research aims to determine whether or not there is an influence of online marketing strategies on consumer buying interest at Toko Jingga. This research uses quantitative methods and uses questionnaires as a tool to collect data. The number of respondents in this research was 100 respondents using purposive sampling technique. The data analysis technique used in this research is simple linear regression analysis using SPSS 25. The results show that online marketing strategies have a positive and significant influence on consumer buying interest at Toko Jingga. This research provides a theoretical impression as a reference for further research related to online marketing and consumer buying interest, especially in online stores. Managerial implications in the form of suggestions for the management of Toko Jingga and other marketplaces to improve product quality and the promotional system used in marketing products so as to increase consumer buying interest.